2016
DOI: 10.1021/acs.jpcb.6b03878
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protein Conformation, Apparent Solubility, and Protein–Protein Interactions on the Rates and Mechanisms of Aggregation for an IgG1Monoclonal Antibody

Abstract: Non-native protein aggregation is a key degradation pathway of immunoglobulins. In this work, the aggregation kinetics of an immunoglobulin gamma-1 monoclonal antibody (IgG1 mAb) in different solution environments was monitored over a range of incubation temperatures for up to seven months using size exclusion chromatography. Histidine and citrate buffers with/without sodium chloride were employed to modulate the mAb's conformational stability, solubility (in the presence of polyethylene glycol, PEG), and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 62 publications
2
48
0
Order By: Relevance
“…These results imply that despite exhibiting lower T onset for conformational changes at pH 5.8, Fab aggregates less at pH 5.8 compared to pH 8.0, indicating that the colloidal stability is playing a major role in Fab aggregation. These results are quite consistent with recent studies which indicated that the colloidal stability can account for the lack of a clear relationship between the conformational stability and aggregation of mAbs 49,50 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results imply that despite exhibiting lower T onset for conformational changes at pH 5.8, Fab aggregates less at pH 5.8 compared to pH 8.0, indicating that the colloidal stability is playing a major role in Fab aggregation. These results are quite consistent with recent studies which indicated that the colloidal stability can account for the lack of a clear relationship between the conformational stability and aggregation of mAbs 49,50 .…”
Section: Resultssupporting
confidence: 93%
“…In the first study on the aggregation behavior of ten different IgG1 antibodies 49 , there was no absolute trend between the conformational stability and aggregation of the IgG1 molecules, implying that colloidal stability plays a major role in IgG1 aggregation. In the second study 50 , changing the solution pH from 6.5 to 4.5 reduced the thermal stability of IgG1; however, less protein aggregation was observed at pH 4.5, because of the increased colloidal stability of the protein. Decreasing pH to acidic values increases the net charge on the protein surface leading to increased repulsive interactions between individual protein molecules, thus leading to an increase in the colloidal stability of the protein.…”
Section: Discussionmentioning
confidence: 89%
“…17 Independently from any other factor, proteins have a certain propensity to self-associate, which has been shown to be particularly implicated in aggregates growth. 66 This phenomenon seems to be governed by electrostatic interactions end by dipole moments between protein surfaces, 67 and might engage preferentially Fab-Fab interactions. 68 Self-association highly impacts solution viscosity and is dependent on the ionic strength of the solution.…”
Section: Protein Structurementioning
confidence: 99%
“…[11][12][13] The protein is exposed to various buffer and salt solutions necessitated by the chromatographic and filtration steps of the process, which can also induce some aggregate formation. [14][15][16][17] Many of the process steps involve filtration, a process that creates a complex set of stress conditions including shear effects, cavitation, localized high concentrations of protein, and interactions at the filter membrane surface. This can even result in the formation of a gel layer 18 which is then sloughed out into the bulk as aggregates and can also act as a nucleus for further aggregate growth.…”
Section: Process Impurities and Microbiological Contaminantsmentioning
confidence: 99%